THE TRANSLATION OF THE LEXEME “RAIN” IN SAPARDI DJOKO DAMONO’S POETRY ANTHOLOGY ”HUJAN BULAN JUNI” INTO MANDARIN CHINESE: A STUDY OF TRANSLATION STRATEGIES - Rachel Leona Davita Purwanto; Tatang Hariri (RADJA PUBLIKA, 2026)
This study analyzes the Mandarin Chinese translation of the poetry anthology